: Perbedaan Skor Clinical Reasoning Mahasiswa Tahap Pre-Klinik Dan Tahap Kepaniteraan Klinik Fakultas Kedokteran Universitas Lampung - Merry Indah Sari; Dwita Oktaria; Aninda Nur Kumalasari; Oktafany (CV. Jasa Sukses Abadi, 2021)
Clinical reasoning is a complex set ideas of diagnosis decision making process that involves those experiences, skill, and reflective thought. Medical faculty students undergoing pre-clinical and clinical students should improve their clinical reasoning as early as possible, so it can produce good quality of medical students. This study aims to determine the difference of clinical reasoning score between pre-clinical and clinical medical students of Lampung University. This was a descriptive analytic study using cross sectional study. Sampling using non-probability sampling method with the type of consecutive sampling and measuring instruments in the form of script concordance test. Data analysis was done by independent T test. The research conducted on 124 respondents with independent test result shows the score of preclinical student with mean 4,927 ± 1.3727 and score of clinical students with mean 5,416 ± 1,6020 with p = 0,041. There are a significant difference clinical reasoning score between pre-clinical and clinical medical students of Lampung University. This study has a significant difference of clinical reasoning score between pre-clinical and clinical medical students of Lampung University. Clinical reasoning in students can be improved by increasing cognition and metacognition through learning self-regulation.